Composite bipolar molecule for water-soluble dual-electrode flow battery system as well as preparation method and application of composite bipolar molecule
By using Viologen and TEMPO composite molecules connected by covalent bonds as dual electrode materials in the flow battery system, the problem of electrode cross-infection is solved, the cycle stability and capacity retention rate of the flow battery are improved, and large-scale energy storage is met application requirements.
Patent Information
- Application Number
- CN202411352451.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-26
AI Technical Summary
There is a problem of electrode cross-infection in existing flow battery systems, which affects the stability and capacity maintenance of the battery, especially in large-scale energy storage applications.
The composite bipolar molecules in the water-soluble dual-electrode liquid flow battery system are used to combine Viologen and TEMPO with covalent bonds as dual-electrode materials to avoid electrode cross-infection and improve circulation stability. The composite molecule is prepared by acid chloride and quaternization reactions and is designed as a bifunctional group that increases solubility and electrochemical activity.
The battery capacity is improved with a capacity retention rate of 51.55%, the capacity decay rate per cycle is 0.095%, and the active material is easy to prepare, with stable charge and discharge performance, meeting the needs of large-scale energy storage.
Smart Images

Figure CN119264112A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid flow batteries, and in particular to a composite bipolar molecule for a water-soluble double-electrode liquid flow battery system, a preparation method thereof, and applications thereof. Background Art
[0002] With the increasing demand for energy and environmental issues, the development and utilization of clean energy is of great significance. However, renewable energy, dominated by wind and solar energy, is inherently volatile and intermittent, and direct grid connection poses stability challenges to the power system. Therefore, the application design of large-scale energy storage system technology is the key to balancing the peak and valley differences of the power grid and achieving stable power supply. Liquid flow battery energy storage, as a new type of large-scale and efficient electrochemical energy storage technology, realizes the mutual conversion and energy storage of electrical energy and chemical energy through the redox valence changes of reactive substances, and has the advantages of flexible design, long life, and high reserves.
[0003] At present, most commercial flow batteries use inorganic materials as active substances, but their high cost and strong toxicity limit the large-scale development of flow batteries. Organic active substances are low-cost, abundant in resources, and easy to adjust molecular energy levels, and have gradually become the focus of research on electrode materials for flow batteries. However, traditional organic small molecule flow battery systems generally have electrode cross-infection problems, which affects the stability of the battery.
[0004] In summary, there is an urgent need for a water-soluble two-electrode liquid flow battery system composite bipolar molecule, which is a water-soluble bipolar composite molecular material. By combining Viologen and TEMPO with excellent electrochemical activity with covalent bonds, it can be simultaneously used as positive and negative electrode materials in the water-soluble two-electrode liquid flow battery cycle, effectively avoiding the irreversible effects of electrode crossover, thereby improving the cycle stability of the battery capacity. Summary of the invention
[0005] The technical problems to be solved by the present invention are:
[0006] Provided are a composite bipolar molecule for a water-soluble two-electrode liquid flow battery system, a preparation method thereof, and an application thereof. The composite bipolar molecule is a water-soluble bipolar composite molecular material. Viologen and TEMPO having excellent electrochemical activity are combined by covalent bonds, and can be simultaneously applied to positive and negative electrode materials in the circulation of a water-soluble two-electrode liquid flow battery, effectively avoiding irreversible effects caused by electrode crossover, thereby improving the cycle stability of the battery capacity.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system, wherein the chemical structural formula of the water-soluble bipolar composite molecule is:
[0009]
[0010] A method for preparing a composite bipolar molecular material for a water-soluble double-electrode liquid flow battery system comprises the following preparation steps:
[0011] S1 uses the nitroxide free radical piperidinol and acyl chloride as raw materials and adds a catalyst to carry out acyl chlorination reaction;
[0012] S2 and 1-propanesulfonic acid-4,4'-bipyridine undergo quaternization reaction to synthesize the water-soluble bipolar composite molecular structure.
[0013] As a further improvement of this scheme, the following preparation steps are specifically included:
[0014] S1 uses the nitrogen oxide free radical piperidinol and acyl chloride as raw materials and adds a catalyst to carry out acyl chlorination reaction
[0015] Add nitroxyl piperidinol and an appropriate amount of solvent into a container, and stir them fully at room temperature; after the solid is completely dissolved, add a catalyst, and stir and deoxygenate in a nitrogen environment; dissolve the acyl chloride in an appropriate amount of solvent, and add it to the above container by dropwise addition; after the dropwise addition is completed, continue to stir and react; after the reaction is completed, filter to remove the precipitate, and wash the filtrate with different extracts in sequence; the obtained organic phase solution is dried to remove water, and then further purified by an alkaline alumina column, and finally the solvent is removed by rotary evaporation to obtain a dark red viscous liquid;
[0016] Among them, the reaction formula of S1 is as follows:
[0017]
[0018] S2 and 1-propanesulfonic acid-4,4'-bipyridine undergo quaternization reaction to synthesize the water-soluble bipolar composite molecular structure
[0019] The dark red viscous liquid obtained in S1 was dissolved in a mixed solvent, and an appropriate amount of 1-propanesulfonic acid-4,4'-bipyridine was added to perform a heating reflux reaction;
[0020] After the reaction is completed, a brown-yellow solid sample is obtained by precipitation with a precipitant;
[0021] Among them, the reaction formula of S2 is as follows:
[0022]
[0023] As a further improvement of this scheme, in S1,
[0024] The catalyst is at least one of pyridine, triethylamine and 4-dimethylaminopyridine;
[0025] The acyl chloride structure is at least one of 5-bromo-valeryl chloride, 5-chloro-valeryl chloride, 4-bromo-butyryl chloride, 4-chloro-butyryl chloride, 3-bromo-propionyl chloride, 3-chloro-propionyl chloride, 2-bromo-acetyl chloride, and 2-chloro-acetyl chloride;
[0026] The organic phase desiccant is at least one of anhydrous sodium sulfate and anhydrous magnesium sulfate;
[0027] The solvent is at least one of dichloromethane, acetonitrile, chloroform, toluene, ethanol, and N,N-dimethylformamide;
[0028] The extract is at least one of deionized water, saturated sodium bicarbonate solution, 2% dilute hydrochloric acid solution, and saturated sodium chloride solution;
[0029] The particle size of the basic alumina in the basic alumina column is one of 100-200 meshes and 200-300 meshes.
[0030] As a further improvement of this scheme, in S1,
[0031] The molar ratio of the raw material nitroxyl free radical piperidinol to the acyl chloride is 1:1 to 1:2;
[0032] The molar ratio of the raw material nitroxyl free radical piperidinol to the catalyst is 1:1 to 1:2;
[0033] The mass percentage of the nitroxide free radical piperidinol in the solvent is 7% to 13%, and the mass percentage of the acyl chloride is 8% to 20%.
[0034] As a further improvement of this scheme, in S1,
[0035] The dropping temperature is 0°C to 5°C, the acyl chlorination reaction temperature is 25°C to 30°C, and the reaction time is 20 to 40 hours.
[0036] As a further improvement of this scheme, in S2,
[0037] The mass percentage of the raw material 1-propanesulfonic acid-4,4'-bipyridine is 10% to 15%, the heating reaction temperature is 65 to 85°C, and the reaction time is 6 to 10 days;
[0038] The volume ratio of the organic phase to the aqueous phase in the mixed solvent is 1:2 to 3:1.
[0039] As a further improvement of this solution, the precipitant is at least one of acetone and cold ethyl acetate;
[0040] The mixed solvent is at least one of N,N-dimethylformamide and water, ethanol and water, acetonitrile and water, and trifluoroethanol and water.
[0041] An application of a composite bipolar molecular material for a water-soluble two-electrode liquid flow battery system. The composite bipolar molecule for the water-soluble two-electrode liquid flow battery system is used in the two-electrode liquid flow battery system. The composite bipolar molecular material can be simultaneously applied to positive and negative electrode materials in the water-soluble two-electrode liquid flow battery cycle.
[0042] As a further improvement of the present scheme, the liquid flow battery system includes: two electrolyte reservoirs and a liquid flow battery stack, the two electrolyte reservoirs are arranged to be spaced apart, each electrolyte reservoir is a storage tank for storing electrolyte or a salt cavern with a physical dissolution cavity formed after salt mining, the battery material is directly dissolved or dispersed in a system with water as a solvent in a bulk form, and the liquid flow battery stack includes a battery diaphragm, which separates the liquid flow battery stack into an anode area and a cathode area that are spaced apart and distributed, the anode area is connected to one electrolyte reservoir, and the cathode area is connected to the other electrolyte reservoir.
[0043] As a further preferred embodiment, the electrolyte concentrations of the positive electrode battery material and the negative electrode battery material are both 0.1 mol·L -1 ~2.5mol·L -1 An inert gas is introduced into the electrolyte reservoir for purging and maintaining pressure. The inert gas is nitrogen or argon.
[0044] The battery separator is an anion exchange membrane, a cation exchange membrane or a porous membrane.
[0045] The supporting electrolyte is NaCl salt solution. The molar concentration of the supporting electrolyte is 0.5 mol·L -1 ~2.0mol·L -1 .
[0046] Compared with the prior art, the present invention has a reasonable design and has the following beneficial effects:
[0047] 1) The present invention uses TEMPO and Viologen as the main body, connects them through covalent bonds, and prepares them into a composite molecular electrode material with dual functional groups, using the ionic groups in the structure to increase its solubility;
[0048] 2) By designing and introducing water-soluble dual-electrode organic small molecules with excellent electrochemical activity as redox couples, a symmetrical flow battery with good stability is obtained;
[0049] 3) After 500 cycles, it decayed to 11.6mAh (theoretical capacity is 40.2mAh, first cycle discharge capacity is 22.5mAh), the capacity retention rate is 51.55%, and the average capacity decay rate per cycle is 0.095%. Using dual-electrode active materials as electrode materials can effectively avoid the irreversible effects caused by cross-contamination between active materials, reduce the decline in battery capacity, improve battery stability, and obtain a liquid flow battery system with the advantages of easy preparation of active materials and stable charge and discharge performance, which can meet large-scale energy storage needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 is a schematic structural diagram of a dual-electrode liquid flow battery system according to an embodiment of the present invention;
[0051] Figure 2 is the H NMR spectrum of the water-soluble bipolar composite molecule prepared in Example 1 in D2O solvent;
[0052] Figure 3 is an ESI-MS image of the water-soluble bipolar composite molecule prepared in Example 1;
[0053] Figure 4 The water-soluble bipolar composite molecule of Example 1 of the present invention (concentration of 3 mg·mL -1 , in a sodium chloride aqueous solution at pH = 7) at different scan rates;
[0054] Figure 5 The charge and discharge capacity diagram of the liquid flow battery system using the water-soluble bipolar composite molecules of Example 1 of the present invention as both positive and negative electrode materials at different current densities;
[0055] Figure 6 This is a forward and reverse charge and discharge voltage-time diagram of a liquid flow battery system using the water-soluble bipolar composite molecules of Example 1 of the present invention as both positive and negative electrode materials;
[0056] Figure 7 This is a cycle stability diagram of a liquid flow battery system using the water-soluble bipolar composite molecules of Example 1 of the present invention as both positive and negative electrode materials;
[0057] Reference numerals:
[0058] Two-electrode flow battery system 100;
[0059] an electrolyte reservoir 20;
[0060] Electrode plate 21; positive and negative electrolyte current collectors 22 and 23; battery separator 24; circulation pump 25. DETAILED DESCRIPTION
[0061] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described below in conjunction with embodiments:
[0062] The positive and negative battery materials of the water-soluble organic liquid flow battery system 100 are the above-mentioned water-soluble bipolar composite molecules, that is, they have both the positive active group 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO) and the negative active group viologen.
[0063] like Figure 1 As shown, the all-polymer liquid flow battery system 100 according to an embodiment of the present invention comprises: two electrolyte reservoirs 20 and a liquid flow battery stack (21-24), the two electrolyte reservoirs 20 are arranged at intervals, each electrolyte reservoir 20 is a storage tank storing electrolyte or a salt cavern with a physical dissolution cavity formed after salt mining, the battery material is directly dissolved or dispersed in a system with water as a solvent in the form of a body, and the liquid flow battery stack comprises a battery separator 24, the battery separator 24 separates the liquid flow battery stack into an anode area and a cathode area that are spaced apart and distributed, the anode area is connected to one electrolyte reservoir 20, and the cathode area is connected to another electrolyte reservoir 20. The design of the dual-functional electrode material can effectively prevent the capacity attenuation problem caused by cross-contamination between ions, thereby improving the cycle stability of the liquid flow battery.
[0064] A water-soluble dual-electrode flow battery system electrode material and a preparation method thereof according to an embodiment of the present invention will be described below with reference to the accompanying drawings.
[0065] In the cyclic voltammetry test, the CH series electrochemical workstation of Shanghai Chenhua Company was used, and the electrochemical properties of the bifunctional small molecule electrode material were tested with a three-electrode system. The working electrode was a glassy carbon electrode (Shanghai Chenhua Company), the reference electrode was an Ag / AgCl electrode, the counter electrode was a platinum electrode, the positive electrode scanning range was 0.2V to 0.8V, and the negative electrode scanning range was -0.8V to -0.2V.
[0066] Example 1
[0067] In a 500mL three-necked flask, add nitrogen oxide free radical piperidinol (33.76g, 196mmol) and dissolve it in 120mL dichloromethane. And dissolve 4-bromo-butyryl chloride (40.06g, 216mmol) in 80ml dichloromethane in advance. Pyridine is used as a catalyst (17.06g, 216mmol). After nitrogen is passed for 30min, 4-bromo-butyryl chloride solution is added drop by drop through a constant pressure dropping funnel under an ice bath environment. After the addition is completed, the ice bath is removed and the reaction is continued at room temperature for 24h. During the reaction, the solution gradually becomes turbid and solids are precipitated. After the reaction is completed, the precipitate is removed by filtration, and the filtrate is washed with deionized water, saturated sodium bicarbonate solution, 2% dilute hydrochloric acid solution, and saturated sodium chloride solution in sequence; the obtained organic phase solution is dried over anhydrous sodium sulfate and further purified by a 100-200 mesh alkaline alumina column; finally, the solvent is removed by rotary evaporation to obtain a dark red viscous liquid 4-(1-oxy-2,2,6,6-tetramethylpiperidine)-4-bromo-4-butyl ester with a yield of 90%.
[0068] The dark red viscous liquid (51.33 g, 160 mmol) from the previous step was dissolved in 300 mL of a mixed solvent of N,N-dimethylformamide and deionized water (volume ratio of 2:1). 1-Propanesulfonic acid-4,4'-bipyridine (42.24 g, 160 mmol) was added and heated to 85°C for 7 days. Acetone precipitation was performed three times to obtain a brown-yellow solid with a yield of 87%.
[0069] Figure 2 is the H NMR spectrum of the water-soluble bipolar composite molecule prepared in Example 1 in D2O solvent;
[0070] Figure 3 This is the ESI-MS image of the water-soluble bipolar composite molecule prepared in Example 1.
[0071] Example 2
[0072] In a 250mL three-necked flask, add the nitrogen oxide free radical piperidinol (20.62g, 120mmol), stir and dissolve it in 100ml dichloromethane, and then add triethylamine as a catalyst (13.64g, 135mmol). Dissolve 4-bromo-butyryl chloride (25.04g, 135mmol) in 50ml dichloromethane in advance. After nitrogen is passed for 30min, add 4-bromo-butyryl chloride solution drop by drop through a constant pressure dropping funnel under an ice bath environment. After the addition is completed, remove the ice bath and continue to react at room temperature for 24h. During the reaction, a light yellow solid precipitates. After the reaction is completed, filter to remove the precipitate, and wash the filtrate with deionized water and saturated sodium chloride solution in turn; the obtained organic phase solution is dried with anhydrous sodium sulfate and further purified through a 100-200 mesh alkaline alumina column. Finally, the solvent was removed by rotary evaporation to obtain a dark red viscous liquid 4-(1-oxy-2,2,6,6-tetramethylpiperidinyl)-4-bromo-4-butyl ester with a yield of 76%.
[0073] The dark red viscous liquid (27.28 g, 85 mmol) from the previous step was dissolved in 180 mL of a mixed solvent of N,N-dimethylformamide and deionized water (volume ratio of 2:1). 1-Propanesulfonic acid-4,4'-bipyridine (21.12 g, 80 mmol) was added and heated to 75°C for 7 days. Acetone precipitation was performed to obtain a brown solid with a yield of 83%.
[0074] Example 3
[0075] In a 250mL three-necked flask, add the nitrogen oxide free radical piperidinol (3.44g, 20mmol), stir and dissolve in 20ml dichloromethane, then add triethylamine (4.04g, 40mmol) and 4-lutidine (0.035g, 1wt%) as catalysts. Dissolve 4-bromo-butyryl chloride (7.42g, 40mmol) in 10ml dichloromethane in advance. After nitrogen is passed for 30min, add 4-bromo-butyryl chloride solution drop by drop through a constant pressure dropping funnel under an ice bath environment. After the addition is completed, remove the ice bath and continue to react at room temperature for 24h. During the reaction, a light yellow solid precipitates. After the reaction is completed, filter to remove the precipitate, and wash the filtrate with deionized water, saturated sodium bicarbonate solution, 2% dilute hydrochloric acid solution, and saturated sodium chloride solution in turn; the obtained organic phase solution is dried with anhydrous sodium sulfate and further purified over an alkaline alumina column. Finally, the solvent was removed by rotary evaporation to obtain a dark red viscous liquid 4-(1-oxy-2,2,6,6-tetramethylpiperidinyl)-4-bromo-4-butyl ester with a yield of 65%.
[0076] Example 4
[0077] In a 500mL three-necked flask, add the nitrogen oxide free radical piperidinol (25.80g, 150mmol), stir and dissolve it in 120ml dichloromethane, and then add triethylamine as a catalyst (16.89g, 165mmol). Dissolve 4-bromo-butyryl chloride (24.98g, 150mmol) in 80ml dichloromethane in advance. After nitrogen is passed for 30min, add 4-bromo-butyryl chloride solution drop by drop through a constant pressure dropping funnel under an ice bath environment. After the addition is completed, remove the ice bath and continue to react at room temperature for 40h. During the reaction, a light yellow solid precipitates. After the reaction is completed, filter to remove the precipitate, and wash the filtrate with deionized water, saturated sodium bicarbonate solution, 2% dilute hydrochloric acid solution, and saturated sodium chloride solution in turn; the obtained organic phase solution is dried with anhydrous sodium sulfate and further purified by a 100-200 mesh alkaline alumina column. Finally, the solvent is removed by rotary evaporation to obtain a dark red viscous liquid with a yield of 82%.
[0078] The dark red viscous liquid (44.94 g, 140 mmol) from the previous step was dissolved in 200 mL of a mixed solvent of N,N-dimethylformamide and deionized water (volume ratio of 3:1). 1-Propanesulfonic acid-4,4'-bipyridine (26.41 g, 100 mmol) was added and heated to 65°C for 10 days. Acetone precipitation was performed three times to obtain a brown solid with a yield of 78%.
[0079] Example 5
[0080] In a 500mL three-necked flask, add the nitrogen oxide free radical piperidinol (18.95g, 100mmol), stir and dissolve it in 100ml dichloromethane, and then add pyridine as a catalyst (9.48g, 110mmol). Dissolve 4-bromo-butyryl chloride (22.20g, 120mmol) in 80ml dichloromethane in advance. After nitrogen is passed for 30min, add 4-bromo-butyryl chloride solution drop by drop through a constant pressure dropping funnel under an ice bath environment. After the addition is completed, remove the ice bath and continue to react at room temperature for 40h. During the reaction, a light yellow solid precipitates. After the reaction is completed, filter to remove the precipitate, and the filtrate is washed with deionized water, saturated sodium bicarbonate solution, 2% dilute hydrochloric acid solution, and saturated sodium chloride solution in turn; the obtained organic phase solution is dried with anhydrous sodium sulfate and further purified by a 100-200 mesh alkaline alumina column. Finally, the solvent is removed by rotary evaporation to obtain a dark red viscous liquid with a yield of 86%.
[0081] The dark red viscous liquid (25.68 g, 80 mmol) from the previous step was dissolved in 200 mL of a mixed solvent of N,N-dimethylformamide and deionized water (volume ratio of 1:1). 1-Propanesulfonic acid-4,4'-bipyridine (26.41 g, 100 mmol) was added and heated to 65°C for 10 days. Acetone precipitation was performed to obtain a brown solid with a yield of 79%.
[0082] Example 6
[0083] In a 250mL three-necked flask, add nitrogen oxide free radical piperidinol (5.16g, 30mmol), stir and dissolve in 50ml dichloromethane, and then add pyridine as a catalyst (2.37g, 30mmol). Dissolve bromoacetyl chloride (5.51g, 35mmol) in 20ml dichloromethane in advance. After nitrogen is passed for 30min, bromoacetyl chloride solution is slowly added dropwise through a constant pressure dropping funnel under an ice bath environment. After the addition is completed, the ice bath is removed and the reaction is continued at room temperature for 24h. During the reaction, a light red solid is precipitated. After the reaction is completed, the precipitate is filtered to remove the precipitate, and the filtrate is washed with deionized water, saturated sodium bicarbonate solution, and saturated sodium chloride solution in turn; the obtained organic phase solution is dried over anhydrous sodium sulfate, and the yield is 51%.
[0084] The dark red viscous liquid (5.38 g, 15 mmol) from the previous step was dissolved in 60 mL of a mixed solvent of anhydrous ethanol and deionized water (volume ratio of 1:2). 1-Propanesulfonic acid-4,4'-bipyridine (6.60 g, 25 mmol) was added and heated to 70°C for 6 days. Acetone precipitation was performed to obtain a brown-red solid with a yield of 60%.
[0085] Example 7
[0086] In a 100mL three-necked flask, add the nitrogen oxide free radical piperidinol (3.44g, 20mmol), stir and dissolve it in 30ml of dichloromethane, and then add pyridine as a catalyst (3.16g, 40mmol). Dissolve 5-bromo-pentanoyl chloride (7.96g, 40mmol) in 20ml of dichloromethane in advance. After nitrogen is passed for 30min, add 5-bromo-pentanoyl chloride solution drop by drop through a constant pressure dropping funnel under an ice bath environment. After the addition is completed, remove the ice bath and continue to react at room temperature for 40h. During the reaction, a light yellow solid precipitates. After the reaction is completed, filter to remove the precipitate, and wash the filtrate with deionized water, saturated sodium bicarbonate solution, 2% dilute hydrochloric acid solution, and saturated sodium chloride solution in turn; the obtained organic phase solution is dried with anhydrous sodium sulfate and further purified by a 100-200 mesh alkaline alumina column. Finally, the solvent is removed by rotary evaporation to obtain a dark red viscous liquid with a yield of 82%.
[0087] The dark red viscous liquid (5.91 g, 15 mmol) from the previous step was dissolved in 60 mL of a mixed solvent of N,N-dimethylformamide and deionized water (volume ratio of 1:1). 1-Propanesulfonic acid-4,4'-bipyridine (5.28 g, 20 mmol) was added and heated to 80°C for 6 days. Acetone precipitation was performed to obtain a brown-red solid with a yield of 75%.
[0088] Results Analysis
[0089] Pyridine and triethylamine are weakly alkaline organic compounds and are also commonly used catalysts for acyl chloride reactions. In the reaction system, they can be used to adsorb HCl produced by the acyl chloride reaction and accelerate the reaction. Compared with triethylamine, using pyridine as a catalyst can better improve the reaction efficiency and product purity. The result may be that when the nitrogen oxide free radical piperidinol is used as a reactant, pyridine can better stabilize the intermediate product and achieve a higher yield. 4-Dimethylpyridine has a similar structure and cooperates with triethylamine as an acyl chloride reaction catalyst. The yield of the obtained product is not high. The result may be that the pyridine structure with dimethyl has no significant effect on the stabilization of the small molecule structure. The results of the acyl chloride reaction under different conditions are shown in Table 1.
[0090] Table 1: Effect of various reaction conditions on the results of acyl chloride reaction
[0091]
[0092] Electrochemical performance testing
[0093] The water-soluble bipolar composite molecule (concentration 3 mg mL) in Example 1 of the present invention was studied by cyclic voltammetry (CV). -1 , in a sodium chloride aqueous solution at pH = 7), wherein the scan rate is 20 mV·s -1 , 50mV·s -1 , 100mV·s -1 , 300mV·s -1 , 500mV·s -1 .
[0094] Figure 4 This is the CV curve of the water-soluble bipolar composite molecule in Example 1 of the present invention.
[0095] The curve shows two groups of redox peaks of the bipolar composite molecule. For the positive active material, it shows a reduction peak of about 0.635V (vs. Ag / AgCl) and an oxidation peak of about 0.712V (vs. Ag / AgCl); for the negative active material, it shows a reduction peak of about -0.547V (vs. Ag / AgCl) and an oxidation peak of about -0.494V (vs. Ag / AgCl). The redox couple thus formed can obtain a theoretical output voltage of about 1.2V.
[0096] Application examples of dual-electrode material flow battery systems
[0097] like Figure 1 As shown in the figure, the structure design of the flow battery as an electrochemical energy storage system mainly includes two independent liquid storage tanks. The electrolyte and the electrochemical device are connected by a pump. The conversion between electrical energy and chemical energy is reversibly coordinated through the electrochemical reaction between the two redox electrode materials. The inside of the battery chamber is separated into an anode chamber and a cathode chamber by an ion exchange membrane. The ion exchange membrane allows specific ions to flow through, thereby balancing the battery charge and preventing cross-infection of active substances.
[0098] 15 mL of a mixed solution of 0.1 M water-soluble bipolar composite molecules in Example 1 of the present invention and 1.5 M NaCl was added to the negative electrode electrolyte tank 22 on the left, and 10 mL of a mixed solution of 0.1 M water-soluble bipolar composite molecules in Example 1 of the present invention and 1.5 M NaCl was added to the positive electrode electrolyte tank 23 on the right. The isolation membrane used an anion exchange membrane AMVN (3.5 cm*3 cm*0.45 cm) to form a bipolar composite molecular liquid flow battery system.
[0099] During the test, first set it to stand for 10s, constant current charging (the current is set to 40mA, 80mA, 100mA, 150mA, 200mA, and the cut-off voltage is ≤1.75V) and constant current discharge (the current is set to 40mA, 80mA, 100mA, 150mA, 200mA, and the cut-off voltage is ≥0.3V), each current density is cycled for 5 times, and finally the test is ended.
[0100] Figure 5 This is the cycling stability diagram of the battery at different current densities.
[0101] Depend on Figure 5 It can be seen that the composite bipolar molecular electrode material has good electrochemical stability. When the current is gradually increased from 40mA to 150mA, the discharge capacity of the battery is maintained at more than 50% of the theoretical value.
[0102] Under the above concentration conditions, the forward and reverse charge and discharge cycle performance test was carried out. In the forward cycle process, the battery was set to stand for 60 seconds, constant current charging (set current to 60mA, cut-off voltage ≤1.75V) and constant current discharge (set current to 60mA, cut-off voltage ≥0.3V), and the cycle test was repeated 5 times; after the reverse cycle process was completed, the battery was set to stand for 60 seconds, constant current discharge (set current to 60mA, cut-off voltage ≥-1.75V) and constant current charging (set current to 60mA, cut-off voltage ≤-0.3V), and the cycle test was repeated 5 times. This cycle was repeated four times, and the test was finally terminated. Figure 6This is the voltage-time diagram of the battery's forward and reverse charge and discharge. During the forward and reverse charge and discharge process, a stable charge and discharge platform can be seen, indicating that the cross-infection problem of the electrodes in the bipolar flow battery system has no irreversible impact.
[0103] Stability test of the bipolar liquid flow battery circulation system. 15 mL of a mixed solution of 0.15 M water-soluble bipolar composite molecules in Example 1 of the present invention and 1.5 M NaCl was added to the negative electrode electrolyte 22 tank on the left, and 10 mL of a mixed solution of 0.15 M water-soluble bipolar composite molecules in Example 1 of the present invention and 1.5 M NaCl was added to the positive electrode electrolyte 23 tank on the right. The isolation membrane uses an anion exchange membrane AMVN (3.5 cm * 3 cm * 0.45 cm) to form a bipolar composite molecular liquid flow battery system. When conducting this test, first set it to stand for 10 seconds, constant current charging (set current to 40 mA, cut-off voltage ≤ 1.75 V) and constant current discharge (set current to 40 mA, cut-off voltage ≥ 0.3 V), cycle test 500 times, and finally end the test. Figure 7 The figure is the cycle stability diagram of the battery. The system has good cycle stability, decaying to 11.6mAh after 500 cycles (theoretical capacity is 40.2mAh, the first cycle discharge capacity is 22.5mAh), the capacity retention rate is 51.55%, and the average capacity decay rate per cycle is 0.095%.
[0104] According to the all-polymer liquid flow battery system 100 of the embodiment of the present invention, a device combining two electrolyte storage reservoirs 20 and a liquid flow battery stack is adopted. The liquid flow battery stack adopts a device combining two electrode plates 21, electrolyte current collectors 22 and 23, a battery separator 24, a circulation pump 25, and a circulation pipeline. The bipolar composite molecules are used as positive and negative electrode materials. The liquid flow battery system 100 has the advantages of easy preparation of active materials and stable charge and discharge performance, and can meet the needs of large-scale energy storage.
[0105] The comparison of the performance of the dual-electrode flow battery system in the prior art and the present invention is shown in Table 2
[0106] Table 2: Comparison of reported performance of dual-electrode flow battery systems
[0107]
[0108] The reference document [1] of the prior art is:
[0109] Liu,T.,et al.,A Total Organic Aqueous Redox Flow Battery Employing aLow Cost and Sustainable Methyl Viologen Anolyte and 4-HO-TEMPOCatholyte. Advanced Energy Materials, 2015.6(3).
[0110] The reference document [2] of the prior art is:
[0111] Winsberg,J.,et al.,TEMPO / Phenazine Combi-Molecule:A Redox-ActiveMaterial for Symmetric Aqueous Redox-Flow Batteries.ACS Energy Letters, 2016.1(5):p.976-980.
[0112] The reference document of the prior art [3] is:
[0113] Janoschka,T.,et al.,An Approach Toward Replacing Vanadium:A SingleOrganic Molecule for the Anode and Cathode of an Aqueous Redox-FlowBattery.ChemistryOpen,2017.6(2):p.216-220.
[0114] The reference document of the prior art [4] is: Gabriel Sikukuu, N., et al., An organic bifunctional redox active material for symmetric aqueous redox flow battery. Nano Energy, 2021.89: p.106422.
[0115] The reference document of the prior art [5] is: Yingzhong, Z., et al., Enhanced cyclability of organic redox flow batteries enabled by an artificial bipolar molecule inneutral aqueous electrolyte. Journal of Power Sources, 2019.417: p.83-89.
[0116] In summary, the water-soluble bipolar composite molecules of the present invention are mainly composed of positive electrode active material TEMPO and negative electrode active material Viologen, which are prepared into bifunctional composite small molecules by first chlorination and then quaternization, and have the following significant advantages: 1. The quaternary ammonium salt and ionic groups on the bipolar composite molecules are used to increase their solubility, thereby further improving the energy density of the battery; 2. Using water-soluble bipolar composite molecules as electrode materials, the positive and negative electrodes use the same active materials to effectively avoid the adverse effects of cross-contamination between active materials, thereby maintaining the stability of the battery capacity. The water-soluble aqueous electrode composite molecular liquid flow battery system 100 of the present invention introduces a composite molecule with excellent positive and negative electrochemical activity as a redox couple through design, and obtains a fully organic bipolar composite molecular liquid flow battery with good stability to meet large-scale energy storage needs.
[0117] The dual-electrode flow battery can avoid the impact of cross-electrode infection and achieve stable circulation in the air.
[0118] The performance comparison of the dual-electrode aqueous flow battery system reported so far is shown in Table 2. In comparison, the bipolar small molecule structure of the present invention not only has the best water solubility, but also has excellent system cycle stability, and is expected to be applied in large-scale flow battery energy storage.
[0119] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.
Claims
1. A composite bipolar molecular material for a water-soluble double-electrode liquid flow battery system, characterized in that: The chemical structural formula of the water-soluble bipolar composite molecule is:
2. A method for preparing a composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system, characterized in that: The method comprises the following preparation steps: S1 uses the nitroxide free radical piperidinol and acyl chloride as raw materials and adds a catalyst to carry out acyl chlorination reaction; S2 and 1-propanesulfonic acid-4,4'-bipyridine undergo quaternization reaction to synthesize the water-soluble bipolar composite molecular structure.
3. The composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system according to claim 2, characterized in that: Specifically comprising the following preparation steps: S1 uses the nitrogen oxide free radical piperidinol and acyl chloride as raw materials and adds a catalyst to carry out acyl chlorination reaction Add nitroxyl piperidinol and an appropriate amount of solvent into a container, and stir them fully at room temperature; after the solid is completely dissolved, add a catalyst, and stir and deoxygenate in a nitrogen environment; dissolve the acyl chloride in an appropriate amount of solvent, and add it to the above container by dropwise addition; after the dropwise addition is completed, continue to stir and react; after the reaction is completed, filter to remove the precipitate, and wash the filtrate with different extracts in sequence; the obtained organic phase solution is dried to remove water, and then further purified by an alkaline alumina column, and finally the solvent is removed by rotary evaporation to obtain a dark red viscous liquid; Among them, the reaction formula of S1 is as follows: S2 and 1-propanesulfonic acid-4,4'-bipyridine undergo quaternization reaction to synthesize the water-soluble bipolar composite molecular structure The dark red viscous liquid obtained in S1 was dissolved in a mixed solvent, and an appropriate amount of 1-propanesulfonic acid-4,4'-bipyridine was added to perform a heating reflux reaction; After the reaction is completed, a brown-yellow solid sample is obtained by precipitation with a precipitant; Among them, the reaction formula of S2 is as follows:
4. The composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system according to claim 3, characterized in that: In S1, The catalyst is at least one of pyridine, triethylamine and 4-dimethylaminopyridine; The acyl chloride structure is at least one of 5-bromo-valeryl chloride, 5-chloro-valeryl chloride, 4-bromo-butyryl chloride, 4-chloro-butyryl chloride, 3-bromo-propionyl chloride, 3-chloro-propionyl chloride, 2-bromo-acetyl chloride, and 2-chloro-acetyl chloride; The organic phase desiccant is at least one of anhydrous sodium sulfate and anhydrous magnesium sulfate; The solvent is at least one of dichloromethane, acetonitrile, chloroform, toluene, ethanol, and N,N-dimethylformamide; The extract is at least one of deionized water, saturated sodium bicarbonate solution, 2% dilute hydrochloric acid solution, and saturated sodium chloride solution; The particle size of the basic alumina in the basic alumina column is one of 100-200 meshes and 200-300 meshes.
5. The composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system according to claim 3, characterized in that: In S1, The molar ratio of the raw material nitroxyl free radical piperidinol to the acyl chloride is 1:1 to 1:2; The molar ratio of the raw material nitroxyl free radical piperidinol to the catalyst is 1:1 to 1:2; The mass percentage of the nitroxide free radical piperidinol in the solvent is 7% to 13%, and the mass percentage of the acyl chloride is 8% to 20%.
6. The composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system according to claim 3, characterized in that: In S1, The dropping temperature is 0°C to 5°C, the acyl chlorination reaction temperature is 25°C to 30°C, and the reaction time is 20 to 40 hours.
7. The composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system according to claim 3, characterized in that: In S2, The mass percentage of the raw material 1-propanesulfonic acid-4,4'-bipyridine is 10% to 15%, the heating reaction temperature is 65 to 85°C, and the reaction time is 6 to 10 days; The volume ratio of the organic phase to the aqueous phase in the mixed solvent is 1:2 to 3:
1.
8. The composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system according to claim 3, characterized in that: The precipitant is at least one of acetone and cold ethyl acetate; The mixed solvent is at least one of N,N-dimethylformamide and water, ethanol and water, acetonitrile and water, and trifluoroethanol and water.
9. An application of a composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system, characterized in that: The composite bipolar molecule for the water-soluble two-electrode liquid flow battery system in claim 1 is used in the two-electrode liquid flow battery system, and the composite bipolar molecule material can be simultaneously applied to the positive and negative electrode materials in the water-soluble two-electrode liquid flow battery cycle.
10. The use of the composite bipolar molecular material for a water-soluble dual-electrode liquid flow battery system according to claim 9, characterized in that: The liquid flow battery system (100) comprises: two electrolyte reservoirs (20) and a liquid flow battery stack (21-24), the two electrolyte reservoirs (20) are arranged at intervals, each electrolyte reservoir (20) is a storage tank storing electrolyte or a salt cavern with a physical dissolution cavity formed after salt mining, the battery material is directly dissolved or dispersed in a system with water as a solvent in the form of a bulk, and the liquid flow battery stack comprises a battery separator (24), the battery separator (24) separates the liquid flow battery stack into an anode area and a cathode area that are distributed at intervals, the anode area is connected to one electrolyte reservoir (20), and the cathode area is connected to the other electrolyte reservoir (20).
Citation Information
Patent Citations
Redox flow cell for storing electrical energy and use thereof
CN108140864A
Dipyridine compound, synthetic method, and symmetric liquid flow battery system thereof
CN110668996A
Preparation method of TEMPO-quaternary ammonium salt for aqueous flow battery
CN114195704A
Ionic cyclic nitroxyl residue oligomers
CN117412957A
Cited By
Multifunctional bi-redox radical organic molecules
WO2026002560A1